2017
DOI: 10.1002/jbm.a.36296
|View full text |Cite
|
Sign up to set email alerts
|

The spatial patterning of RGD and BMP‐2 mimetic peptides at the subcellular scale modulates human mesenchymal stem cells osteogenesis

Abstract: Engineering artificial extracellular matrices, based on the biomimicry of the spatial distribution of proteins and growth factors within their native microenvironment, is of great importance for understanding mechanisms of bone tissue regeneration. Herein, photolithography is used to decorate glass surfaces with subcellular patterns of RGD and BMP-2 ligands; two mimetic peptides recognized to be involved in stem cells osteogenesis. The biological relevance of well-defined RGD and BMP-2 patterned surfaces is ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 60 publications
(141 reference statements)
1
42
0
Order By: Relevance
“…In one example, RGD and BMP peptides that promote cell adhesion and differentiation, respectively, have been micropatterned on glass substrates. 132 These substrates were fabricated by first functionalizing the surface so that it presented maleimide groups, upon which was coated a positive photoresist. Removal of the resist in the photoexposed areas revealed the maleimide groups that were used to capture thiol-presenting peptides.…”
Section: Applications Of Large-scale Lithographic Technologiesmentioning
confidence: 99%
“…In one example, RGD and BMP peptides that promote cell adhesion and differentiation, respectively, have been micropatterned on glass substrates. 132 These substrates were fabricated by first functionalizing the surface so that it presented maleimide groups, upon which was coated a positive photoresist. Removal of the resist in the photoexposed areas revealed the maleimide groups that were used to capture thiol-presenting peptides.…”
Section: Applications Of Large-scale Lithographic Technologiesmentioning
confidence: 99%
“…Many clinical studies have demonstrated the excellent osteoinductivity of bone morphogenetic proteins (BMPs), especially BMP-2, but the direct use of BMP-2 in bone regeneration is hindered by its high cost and short half-life [5,6]. Therefore, the BMP-2-like osteogenic peptide, a safe and cost-effective synthetic osteoinductive peptide, has been increasingly used as a potent alternative to induce osteogenesis [7,8]. Generally, the rapid release and degradation of osteoinductive drugs compromise their function.…”
Section: Introductionmentioning
confidence: 99%
“…Given the biological synergy already observed between co-conjugated peptides on surfaces, in terms of differentiation, it is suggested that this synergistic behavior could also be observed with OGP as one of the conjugated peptides. 20,21 The goal of this study was therefore to develop surfaces with different peptides tethered onto the surface of PET material with a well-controlled density. PET material was chosen for its easy surface modification and as a model material.…”
Section: Introductionmentioning
confidence: 99%